2011
DOI: 10.1007/s10194-010-0282-4
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and psychiatric comorbidity: a review of clinical findings

Abstract: Migraine is an extremely common disorder. The underlying mechanisms of this chronic illness interspersed with acute symptoms appear to be increasingly complex. An important aspect of migraine heterogeneity is comorbidity with other neurological diseases, cardiovascular disorders, and psychiatric illnesses. Depressive disorders are among the leading causes of disability worldwide according to WHO estimation. In this review, we have mainly considered the findings from general population studies and studies on cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
272
2
18

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 334 publications
(309 citation statements)
references
References 73 publications
17
272
2
18
Order By: Relevance
“…Epidemiological studies have established a strong association between primary headaches and psychiatric disorders and the reported rates ranged between 56.4-70.3% in migraine and 36.4-77.8 % in TTH [30,[48][49][50][51][52] . In one study, 29.6% of CDH patients met criteria for at least one current psychiatric diagnosis, and 34.9% met criteria for at least one-lifetime psychiatric diagnosis [53] .…”
Section: Co-morbiditiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Epidemiological studies have established a strong association between primary headaches and psychiatric disorders and the reported rates ranged between 56.4-70.3% in migraine and 36.4-77.8 % in TTH [30,[48][49][50][51][52] . In one study, 29.6% of CDH patients met criteria for at least one current psychiatric diagnosis, and 34.9% met criteria for at least one-lifetime psychiatric diagnosis [53] .…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…In one study, 29.6% of CDH patients met criteria for at least one current psychiatric diagnosis, and 34.9% met criteria for at least one-lifetime psychiatric diagnosis [53] . Depressive and anxiety disorders being the common disorders, other being dysthymia, phobic disorder, obsessive compulsive disorder, somatoform disorders, sleep difficulties and disorders (insufficient and poorer sleep quality, co-sleeping with parents, anxiety related to sleep, night waking, nightmares, bedwetting and pavor), suicidal ideation and an increased risk of suicidality [30,48,[50][51][52][54][55][56][57][58][59][60][61] .The lifetime prevalence of major depression was threefold higher in persons with migraine and in persons with a severe headache compared with controls [62] .TTH is associated with fewer close friends and had a higher rate of divorced parents [63] . Previous studies have shown a significant negative correlation between total intelligence quotient, verbal intelligence quotient, performance intelligence quotient and the frequency of headache attacks [64] .…”
Section: Co-morbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…There is overwhelming evidence demonstrating the comorbidity of psychiatric illness in patients with migraine [81,82]. Studies suggest mood and anxiety disorders generate the most prevalent subset, with more than 47 % of migraineurs meeting criteria for these conditions [83,84].…”
Section: Does the Amygdala Contribute To Migraine Pain?mentioning
confidence: 99%